A single nucleotide polymorphism variant located in the cis‐regulatory region of the ABCG2 gene is associated with mallard egg colour. Issue 6 (3rd March 2021) - Liu, Hehe; Hu, Jian; Guo, Zhanbao; Fan, Wenlei; Xu, Yaxi; Liang, Suyun; Liu, Dapeng; Zhang, Yunsheng; Xie, Ming; Tang, Jing; Huang, Wei; Zhang, Qi; et al.
Abstract: Avian egg coloration is shaped by natural selection, but its genetic basis remains unclear. Here, we used genome‐wide association analysis and identity by descent to finely map green egg colour to a 179‐kb region of Chr4 based on the resequencing of 352 ducks ( Anas platyrhynchos ) from a segregating population resulting from the mating of Pekin ducks (white‐shelled eggs) and mallards (green‐shelled eggs). We further narrowed the candidate region to a 30‐kb interval by comparing genome divergence in seven indigenous duck populations. Among the genes located in the finely mapped region, only one transcript of the ABCG2 gene (XM_013093252.2) exhibited higher uterine expression in green‐shelled individuals than in white‐shelled individuals, as supported by transcriptome data from four populations. ABCG2 has been reported to encode a protein that functions as a membrane transporter for biliverdin. Sanger sequencing of the whole 30‐kb candidate region (Chr4: 47.41–47.44 Mb) and a plasmid reporter assay helped to identify a single nucleotide polymorphism (Chr4: 47, 418, 074 G>A) located in a conserved predicted promoter region whose variation may alter ABCG2 transcription activity. We provide a useful molecular marker for duck breeding and contribute data to the research on ecological evolution based on egg colour patterns among birds.